2009
DOI: 10.1007/s00419-009-0340-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of turbulent free jet flows issuing from rectangular nozzles: the influence of small aspect ratio

Abstract: In this research, the fluid and thermal characteristics of a rectangular turbulent jet flow is studied numerically. The results of three-dimensional jet issued from a rectangular nozzle are presented. A numerical method employing control volume approach with collocated grid arrangement was employed. Velocity and pressure fields are coupled with SIMPLEC algorithm. The turbulent stresses are approximated using k-ε model with two different inlet conditions. The velocity and temperature fields are presented and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…Also it should be mentioned that the experiment of Quinn [1] and Quinn and Militzer [21] does not have the same Reynolds number ( [1] in Re = 1.84 × 10 5 and [21] in Re = 2.08 × 10 5 ). This is supported by Malmstrom et al [36], Mi et al [37] and Faghani et al [27,28] who showed that the mean flow quantities are independent of Reynolds number for the Reynolds numbers higher than a critical value. Figure 9 shows the decay of mean streamwise velocity along the centerline for a contoured nozzle in the near-field region.…”
Section: Contoured Nozzlementioning
confidence: 56%
See 1 more Smart Citation
“…Also it should be mentioned that the experiment of Quinn [1] and Quinn and Militzer [21] does not have the same Reynolds number ( [1] in Re = 1.84 × 10 5 and [21] in Re = 2.08 × 10 5 ). This is supported by Malmstrom et al [36], Mi et al [37] and Faghani et al [27,28] who showed that the mean flow quantities are independent of Reynolds number for the Reynolds numbers higher than a critical value. Figure 9 shows the decay of mean streamwise velocity along the centerline for a contoured nozzle in the near-field region.…”
Section: Contoured Nozzlementioning
confidence: 56%
“…But the results of Berg et al [22] show some deviation, especially in the spread of jet and the streamwise velocity profile at the near field of the inlet. Faghani et al [27,28] simulated the flow from different nozzle shapes. In this research, higher turbulence intensity was used to simulate flow through a sharp-edged nozzle.…”
mentioning
confidence: 99%
“…Recently Faghani et al [22] reported an investigation of the inflow condition of a rectangular turbulent jet on the mean flow properties. A uniform velocity profile at the nozzle exit with two turbulence intensities, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Regard to mixing and entrainment phenomenon in free jets and also due to overcoming of inertia forces to viscous forces, gas leakage from tanks has turbulent nature [19]. In numerical modeling using Boussinesq approximation, turbulence terms in momentum equations (Reynolds stresses) get related to gradient of average velocities according to Eq(11) [20,21]:…”
Section: Turbulence Modelingmentioning
confidence: 99%
“…TKE is kinematic energy of velocity fluctuations and TI is turbulence intensity which was calculated using Eq (19):…”
Section: Turbulence Fieldmentioning
confidence: 99%